A transcriptomics-based analysis of the toxicity mechanisms of gabapentin to zebrafish embryos at realistic environmental concentrations. (August 2019) - He, Yide; Li, Xiuwen; Jia, Dantong; Zhang, Wenming; Zhang, Tao; Yu, Yang; Xu, Yanhua; Zhang, Yongjun
Abstract: Gabapentin (GPT) has become an emerging contaminant in aquatic environments due to its wide application in medical treatment all over the world. In this study, embryos of zebrafish were exposed to gabapentin at realistically environmental concentrations, 0.1 μg/L and 10 μg/L, so as to evaluate the ecotoxicity of this emergent contaminant. The transcriptomics profiling of deep sequencing was employed to illustrate the mechanisms. The zebrafish ( Danio rerio ) embryo were exposed to GPT from 12 hpf to 96 hpf resulting in 136 and 750 genes differentially expressed, respectively. The results of gene ontology (GO) analysis and the Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis illustrated that a large amount of differentially expressed genes (DEGs) were involved in the antioxidant system, the immune system and the nervous system. RT-qPCR was applied to validate the results of RNA-seq, which provided direct evidence that the selected genes involved in those systems mentioned above were all down-regulated. Acetylcholinesterase (AChE), lysozyme (LZM) and the content of C-reactive protein (CRP) were decreased at the end of exposure, which is consistent with the transcriptomics results. The overall results of this study demonstrate that GPT simultaneously affects various vital functionalities of zebrafish at early developmental stage, even at environmentally relevant concentrations. Graphical abstract: Image 1 Highlights: The ecotoxicity of gabapentin to zebrafish embryos was measured. Transcriptomic techniques were applied to illustrate the underlying mechanisms. The antioxidant, immune and nervous system of zebrafish were significantly affected. Abstract : The present study illustrates the toxic effects of gabapentin to zebrafish at early developmental stage at environmentally relevant concentrations, and the mechanisms behind.